Effect of Dry Needling on Thigh Muscle Strength and Hip Flexion in Elite Soccer Players - Haser, Christian; Stoeggl, Thomas; Kriner, Monika; Mikoleit, Joerg; Wolfahrt, Bernd; Scherr, Johannes; Halle, Martin; Pfab, Florian (Medicine and science in sports and exercise, 2017)
Purpose Increase in muscle force, endurance, and flexibility is desired in elite athletes to improve performance and to avoid injuries, but it is often hindered by the occurrence of myofascial trigger points. Dry needling (DN) has been shown effective in eliminating myofascial trigger points. Methods This randomized controlled study in 30 elite youth soccer players of a professional soccer Bundesliga Club investigated the effects of four weekly sessions of DN plus water pressure massage on thigh muscle force and range of motion of hip flexion. A group receiving placebo laser plus water pressure massage and a group with no intervention served as controls. Data were collected at baseline (M1), treatment end (M2), and 4 wk follow-up (M3). Furthermore, a 5-month muscle injury follow-up was performed. Results DN showed significant improvement of muscular endurance of knee extensors at M2 (P = 0.039) and M3 (P = 0.008) compared with M1 (M1:294.6 ± 15.4 N·m·s-1, M2:311 ± 25 N·m·s-1; M3:316.0 ± 28.6 N·m·s-1) and knee flexors at M2 compared with M1 (M1:163.5 ± 10.9 N·m·s-1, M2:188.5 ± 16.3 N·m·s-1) as well as hip flexion (M1: 81.5° ± 3.3°, M2:89.8° ± 2.8°; M3:91.8° ± 3.8°). Compared with placebo (3.8° ± 3.8°) and control (1.4° ± 2.9°), DN (10.3° ± 3.5°) showed a significant (P = 0.01 and P = 0.0002) effect at M3 compared with M1 on hip flexion; compared with nontreatment control (-10 ± 11.9 N·m), DN (5.2 ± 10.2 N·m) also significantly (P = 0.049) improved maximum force of knee extensors at M3 compared with M1. During the rest of the season, muscle injuries were less frequent in the DN group compared with the control group. Conclusion DN showed a significant effect on muscular endurance and hip flexion range of motion that persisted 4 wk posttreatment. Compared with placebo, it showed a significant effect on hip flexion that persisted 4 wk posttreatment, and compared with nonintervention control, it showed a significant effect on maximum force of knee extensors 4 wk posttreatment in elite soccer players.
CRIS-Team Scopus Importer:2023-03-08
Keywords: ATHLETES; DRY NEEDLING; ENDURANCE; FORCE; MOBILITY; MUSCLE INJURIES; SOCCER